(untitled) (Journal of Tropical Pharmacy and Chemistry, 2015)
Screening Ageratum conyzoides L. fraction for antibacterial activity using thin layer chromatography bioautography have been done. The method is based on thin-layer chromatography–direct bioautography of Ageratum conyzoides chloroform fraction. The aim of study to determine the antibacterial activity of chloroform Ageratum conyzoides L. fraction in TLC bioautography. Extraction was done by maceration using methanol solvent, followed by partition using chloroform solvent using liquid-liquid extraction method is done by chromatographic profile of each eluent comparison is then performed further fractionated using vacuum liquid chromatography method. Screening activity of the compound was done qualitatively raction results are antibacterial activity test using thin layer chromatography bioautography The results showed that the eluent to separate the components of a compound based on the chomatography profile is eluent n-hexane: ethyl acetate (2: 1), the results obtained by fractionation of the active fraction (51-53) Rf value of 0.59. Results of screening activity held chloroform fraction Ageratum conyzoides leaves are antibacterial activity which can be seen from the formation of inhibition zones in the region stain spot on the TLC plate were grown in glucose medium Nutrient. The results were analyzed descriptively, that is to describe the characteristics of the research which is obtained.